2022
DOI: 10.2196/38943
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach for Continuous Mining of Nonidentifiable Smartphone Data to Create a Novel Digital Biomarker Detecting Generalized Anxiety Disorder: Prospective Cohort Study

Abstract: Background Anxiety is one of the leading causes of mental health disability around the world. Currently, a majority of the population who experience anxiety go undiagnosed or untreated. New and innovative ways of diagnosing and monitoring anxiety have emerged using smartphone sensor–based monitoring as a metric for the management of anxiety. This is a novel study as it adds to the field of research through the use of nonidentifiable smartphone usage to help detect and monitor anxiety remotely and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Generally, they also showed more active application engagement in the early hours or midnight compared to healthy controls, who showed diluted engagement patterns throughout the day. Meanwhile, Choudhary et al [ 212 ] revealed that individuals with anxiety exhibited more frequent usage of applications from “passive information consumption apps”, “games”, and “health and fitness” categories.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, they also showed more active application engagement in the early hours or midnight compared to healthy controls, who showed diluted engagement patterns throughout the day. Meanwhile, Choudhary et al [ 212 ] revealed that individuals with anxiety exhibited more frequent usage of applications from “passive information consumption apps”, “games”, and “health and fitness” categories.…”
Section: Resultsmentioning
confidence: 99%
“…XGBoost and AdaBoost were gradually favored by researchers due to their better predictive performance. Specifically, few studies [ 134 , 158 , 184 , 212 ] revealed XGBoost as the most effective among SVM, RF, K-nearest neighbor, logistic regression, and DNN models. In contrast, researchers also proposed novel hierarchical ensemble architectures by stacking algorithms (e.g., XGBoost [ 194 ], Extreme Learning Machine (ELM) [ 192 ]) into layers where models in subsequent layers receive outputs from previous layers as inputs for ensemble predictions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accelerometer data, app use, number of text messages and phone calls, and GPS-derived measures (number of distinct locations visited, number of hours outside, distance traveled) were used to detect depressive and manic episodes in bipolar patients with high precision and recall rates 62,63 . In a recent study 64 , a new metric, the Mental Health Similarity Score, derived from passively collected smartphone app use data, for tracking individual-level daily anxiety levels, was shown to correlate with the 7-item Generalized Anxiety Disorder Scale 65 . App use data were also used in the context of sleep, mood, and stress 57,[66][67][68] .…”
Section: The Potential Of Mobile Health and Ai To Augment Cognitive A...mentioning
confidence: 99%